2013
DOI: 10.1590/s0100-736x2013000900015
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos da morfologia radiográfica do esqueleto, tórax e abdome do quati (Nasua nasua Linnaeus, 1766)

Abstract: Treze quatis (Nasua nasua) oriundos do Parque Zoológico da Universidade Federal do Mato Grosso foram contidos quimicamente e submetidos a diversos procedimentos radiográficos. Foram realizadas radiografias dos membros torácicos, membros pélvicos, tórax, abdome, pescoço e crânio. As imagens obtidas foram comparadas com peça anatômica e com imagens radiográficas de caninos. Foram realizadas descrições da morfologia radiográfica de vísceras e de estruturas esqueléticas e disponibilizadas imagens das principais pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
(8 reference statements)
0
3
1
Order By: Relevance
“…In one coati, physical therapy, which is considered to increase the possibility of recovery (25), was also realized. Interestingly, anatomical findings of the vertebral column in the two coatis differ from the description of the number of vertebrae in 13 coatis investigated previously (22). In this radiographic study, coatis were found to have 15 thoracic and five lumbar vertebrae.…”
Section: Discussioncontrasting
confidence: 85%
“…In one coati, physical therapy, which is considered to increase the possibility of recovery (25), was also realized. Interestingly, anatomical findings of the vertebral column in the two coatis differ from the description of the number of vertebrae in 13 coatis investigated previously (22). In this radiographic study, coatis were found to have 15 thoracic and five lumbar vertebrae.…”
Section: Discussioncontrasting
confidence: 85%
“…The radiological visualisation of the os penis in this species should not be mistaken as soft tissue mineralisation. The os penis is also seen in the domestic dog [ 47 ], ring-tailed lemur [ 24 ], red panda [ 22 ], and coati [ 23 ] on radiological examination.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the normal radiological anatomy of specific species and high standard radiographs are significant for accurate radiological diagnosis [ 16 ]. Normal radiological anatomy of the pelvis and pelvic limb in other rodents [ 17 20 ] and captive animals such as the hedgehog [ 21 ], red panda [ 22 ], coati [ 23 ], ring-tailed lemur [ 24 ], and nondomestic cats [ 25 ] have been reported, which serve as a reference for identification of musculoskeletal conditions and diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Only in the procyonid N. nasua and in the mephitids C. chinga and C. semistriatus not even histological traces of the clavicle were found. Martins et al (2013) approached the radiographic anatomy of the skeleton based on 13 specimens of N. nasua and also did not mention the presence of this bone.…”
Section: Discussionmentioning
confidence: 99%